FEAR, EXCITEMENT AND HISTORIOGRAPHY - Timmermann López, Freddy (Revista de Historia Social y de las Mentalidades, 2015)
Through the elements of emotion and fear,  theoretical relationships to historiography are  established, which determines your analytical  capabilities. The relevance of building emotional  contexts in the study of historiographic objects  from a methodology focused on the analysis  of discourse in the construction of textual  macroforms of fear and its contextual projection.  It expands, thus, the understanding of the  historical processes by which the individual  apprehends and significantly orders his social  reality.
Keywords: Fear; Emotion; Historiography; Insecurity; Textual macrostructures